Key concepts in e-commerce - Charlesworth, Alan 1956- (Palgrave key concepts, 2007)
E-Commerce is making an ever-bigger impact on the way businesses operate. Key Concepts in e-Commerce offers readers an introduction to the many words, terms and phrases that abound in this fast developing and increasingly popular discipline.